OEDI cycle for the setting up of a pilot cocoa processing plant - Cohecha.Realpe, Cristian C. (2022)
Objective. To implement the OEDI cycle to configure the assembly of a pilot plant for cocoa processing in the municipality of Frontino, Antioquia (Colombia), as part of the SENA Project, Cocoa 4.0. Methods. The methodology offered a strategic management tool of great importance for the industrial and food sector, using conceptual and operational learning that generated different administrative bases in the strengthening of transversal axes (attenuators and amplifiers), which were developed during the project. This allowed defining different performance criteria to achieve a better management of complexity in a specific situation. By establishing the links of the OEDI cycle, changes were generated in the synergy of the project in which different actors intervene in the supply chain, where communication is absolutely necessary to meet the requested requirements. Results. It is highlighted that the proper implementation of the OEDI cycle facilitated the generation of positive synergies within each phase, turning these into attenuators and amplifiers that allowed guiding the management of complexity. Conclusion. One of the most important challenges in the implementation of the cycle was to ensure that the project's complexity management was understood and developed from the application of performance criteria by each actor in the supply chain, both in the requirement of materials, equipment and production flows, given the technical conditions of the project in the assembly of the cocoa processing pilot plant.